CONSTRUCTING A STRUCTURAL-FUNCTIONAL MODEL OF SOCIAL EXPECTATIONS OF THE PERSONALITY - Popovych, Ihor; Borysiuk, Alla; Zahrai, Larysa; Fedoruk, Oleksandra; Nosov, Pavlo; Zinchenko, Sergiy; Mateichuk, Vadym (Revista Inclusiones, 2020)
The purpose of the study is to construct and substantiate the structural-functional model of social expectations of the personality. A completely new approach to understanding and organizing the study of social expectations of the personality is proposed. Social expectations as a process and result of a person’s mental activity are theoretically substantiated. The methodology of the study was a systematic approach which allowed to solve the problem holistically. It was determined the verified system of principles on which the modeling of social expectations of the personality was based. It is stated that the following principles are based on the development of the structuralfunctional model: systematicity and integrity of the researched subject, complex approach to the research subject, reflection of the internal and external world of the research subject, interdependence of internal and external factors of the research, principle of functionality and social determinism of the researched subject, the principle of subjectivity. The structural and functional model of social expectations of personality was constructed, which allowed to study internal